Russia Germans in Kalmykia: Milestones of History — Milestones of Fate - Rayma G. Saryaeva (Oriental Studies, 2022)
Introduction. The 260-year history of Russia Germans is still of interest to researchers. The Germans of Kalmykia, their history, life and culture remain somewhat understudied. Goals. The work aims at revealing circumstances to have surrouned the arrival and strengthening of Germans in Kalmykia, analyzes available sources for an overview of historical milestones experienced by the ethnic group in the Republic. To facilitate this, the paper shall consider reasons of the German immigration to Russia, provide a comprehensive description of the latter, reveal causes of the subsequent deportation and problems of rehabilitation and emigration. Materials. The study investigates archival sources, publications dealing with the history of Russia Germans, periodicals and author’s field data. Results. The analysis of sources yields a history of Kalmykia Germans from their arrival in nomadic territories of Bolshederbetovsky Ulus to the modern era. The perestroika witnessed mass migrations of Kalmykia Germans back to Germany to have resulted from the loss of mother tongue, and harsh economic conditions.